The status of water resources in the piedmont and its management - Zicari, Giuseppe (Progress in Nutrition, 2015)
Introduction: Surface water and groundwater are renewable natural resources, provided they are used in a sustainable way. Some indicators show the wasting of water resources and its lower availability: it loses between 30% and 50% of the water during distribution, up to 30% of water is used improperly, for example, to irrigate; some aquifers provide less and less water. The water resource quality tends to get worse: in Piedmont there are at least 500 industrial or waste treatment sites for which it was necessary to activate the procedure for remediation of contamination which have also generated the pollution of surface water and groundwater, and in this Region gravitate around 14,000,000 animals such as cattle, poultry and pigs. Objectives and methods: In this study we present some results obtained from the monitoring of groundwater and surface water made by the Health Service in Piedmont and we consider some problems such as contamination generated by crops (plant protection products), from breeding (nitrates) and others (chlorinated solvents). We also commented on certain information submitted on institutional web sites (eg census regional breeding, agriculture, waste). Results: - For every 10,000 square feet of surface cultivated in Piedmont there is the availability of manure derived from 2 cows, 3 pigs, 22 chickens, 700 kg of compost from municipal solid waste and up to 200 kg of sludge from waste water treatment plants. - 35% of the sampling points of ground water examined in Piedmont showed a high level of impairment (eg due to the presence of plant protection products). - Less than 15% of the points of groundwater sampled in the Province of Vercelli appeared without plant protection products (area where there is a widespread rice cultivation). - 54% of groundwater monitoring points, in the Province of Turin, contains chlorinated solvents. - The study conducted on 192 among the present 967 in Piedmont, led to the following conclusions for 185 rivers (Directive 2000/60/EC): - 109 are at risk; - 59 are probably at risk; - 17 are not at risk. - In 2012, in Piedmont we can classify as vulnerable areas, because of the nitrates found in water, approximately 402,377 ha: 38% of the utilized agricultural regional area and 54% of the surface of the plain. Conclusions: Many hundreds of thousands of different chemicals are distributed in large quantities in the environment and you have information about the hazards just for a small part of them. The only analytical control cannot reassure ourselves about the health of the waters. We need to invest in a better prevention of water resources contamination and towards a more sustainable and rational utilization.